PERAN KEPERCAYAAN MEREK ( BRAND TRUST) TERHADAP LOYALITAS MEREK PRODUK SUSU MEREK SGM (PADA IBU-IBU PASANGAN USIA SUBUR DI POSYANDU MELATI 14 DESA PURWOKERTO LOR, KABUPATEN BANYUMAS) - arinastuti; harsuti (Majalah Imiah Manajemen & Bisnis, 2020)
This study is entitled "The Role of Brand Trust on Brand Loyalty of SGM Brand Dairy Products. The purpose of this study was to determine the significance of the influence of brand characteristics, company characteristics and brand-consumer characteristics on brand loyalty in SGM milk products consumers The research hypothesis is brand characteristics, company characteristics and brand-consumer characteristics have a significant influence on brand loyalty in SGM dairy product consumers To test the effect of the independent variables on the dependent variable used multiple linear regression analysis. Based on these analysts results obtained tX1 of 2,773, tX2 of 2,802 and tX3 of 4,406 greater than t table of 2,030 so that Ho is rejected or Ha is accepted. Therefore the first, second, third hypothesis is accepted.